PEMANFAATAN PELET KULIT JENGKOL (Archidendronpauciflorum) PADA RANSUM TERNAK DOMBA DAN PENGARUHNYA TERHADAP NH3 DAN POPULASI PROTOZOA - Raindri; Nurhaita, Nurhaita (Fakultas Pertanian dan Peternakan Universitas Muhammadiyah Bengkulu, 2023)
This study aims to know the effect of adding jengkol peel pellets containing bio-active substances of tannins and saponins in sheep ration on NH3 and Protozoa population. This study used a randomized block design (RBD) with 3 treatments and 5 replications. The treatment given P1 = concentrate (40%) + natural grass (60%), P2 = concentrate (40%) + field grass (45%) + jengkol peel (15%) P3 = concentrate (40%) + field grass ( 37.5%) + Jengkol peel (22.5%) The parameters observed were NH3 and the Protozoa population. The data were analyzed by using anova variety analysis. The results of this study showed that the use of jengkol peel pellets (15% - 22.5%) in sheep rations has very significant effect (P <0.01) on NH3 and protozoa population. In this study, there was an increase in NH3 and a decrease in the rumen protozoan population. The conclusion of this study is the best use of jengkol peel pellets is in the level of 22.5% can increase NH3 and reduce the population of rumen protozoa. Keywords: Jengkol Peel Pellets (Archidendron Pauciflorum), NH3, and Protozoa Populations.